2008
DOI: 10.1111/j.1744-7348.2008.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to selection for grain yield and correlated response for grain size and earliness in cowpea based on early generation testing

Abstract: Large grain size and earliness to flowering are traits critical to cowpea adoption in the West African savannahs. This study reports on the correlated response to selection in these two traits in the two populations in which selections were made primarily for grain yield potential. Further, the present study reports on the effectiveness of early generation selection for grain yield. Each of the two populations, SARC 2 and SARC 3, was derived from a cross between an adapted parent Marfo-Tuya and an exotic breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
5
0
2
Order By: Relevance
“…It was able to recover quickly from drought during the growing season and produce higher yields. This corroborates many drought study by [23,24] Padi-tuya produce higher yield in the first, third and fourth planting date, and had the second highest yield in the second planting date. The genotype T 2 T 4 also gave appreciable yield in the second planting date, and produces the second highest yield in the first second and third planting dates.…”
Section: Yield and Yield Componentssupporting
confidence: 90%
“…It was able to recover quickly from drought during the growing season and produce higher yields. This corroborates many drought study by [23,24] Padi-tuya produce higher yield in the first, third and fourth planting date, and had the second highest yield in the second planting date. The genotype T 2 T 4 also gave appreciable yield in the second planting date, and produces the second highest yield in the first second and third planting dates.…”
Section: Yield and Yield Componentssupporting
confidence: 90%
“…The low estimate of heritability for days to flowering based on parent-hybrid regression is not surprising. The dominance of earliness to flower over lateness to flower in cowpea is well known but with few genes underlying this trait selection should be effective in the early generations (Padi, 2008). Among these traits, the hundred seed weight (a measure of grain size) is the most important to consumers, directly influencing the market value of cowpea grains in West Africa ((Langyintuo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The haulms are used as fodder for livestock particularly during the dry season (Blade et al, 1997). Although cowpea contributes significantly to the income of farmers in the northern savannah zones of West Africa where varieties with grain yield potentials in excess of 3.0 t/ha have been developed for cultivation, farm level yields of cowpea are within the range of 0.3 to 0.65 t/ha (SARI, 1996 and1997).…”
Section: Introductionmentioning
confidence: 99%
“…Adeyanju and Ishiyaku (2007) reported that earliness is an important agronomic trait, and it is important for cowpea in areas with relatively short rainfall cycle. Padi (2007) mentions that grain size and earliness are essential traits for the adoption of cowpea cultivars in the savannas of West Africa.…”
Section: Introductionmentioning
confidence: 99%